2014
DOI: 10.3171/2014.6.gks14708
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery to the resection bed for intracranial metastases and risk of leptomeningeal carcinomatosis

Abstract: ObjectFollowing resection of a brain metastasis, stereotactic radiosurgery (SRS) to the cavity is an emerging alternative to postoperative whole-brain radiation therapy (WBRT). This approach attempts to achieve local control without the neurocognitive risks associated with WBRT. The authors aimed to report the outcomes of a large patient cohort treated with this strategy.MethodsA retrospective review identified 91 patients without a history of WBRT who received Gamma Knife (GK) SRS to 96 metastasis resection c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 48 publications
6
63
1
Order By: Relevance
“…The addition of postoperative WBRT has been shown to reduce the risk of both local and distal tumor recurrence within the brain compared to surgery alone, with an absolute risk reduction of 36% (5 [10%] of 49 vs 21 [46%] of 46, P < .001) and 23% (7 [14%] of 49 vs 17 [37%] of 46, P < .01) for local and distal tumor recurrence, respectively, as reported in Patchell et al's landmark study in 1998 . However, the use of WRBT is limited by an associated increased risk of neurocognitive decline and decreased QOL . As patient survival improves, these long‐term toxicities are becoming less acceptable.…”
Section: The Role Of Adjuvant/neoadjuvant Therapies and Surgerymentioning
confidence: 87%
“…The addition of postoperative WBRT has been shown to reduce the risk of both local and distal tumor recurrence within the brain compared to surgery alone, with an absolute risk reduction of 36% (5 [10%] of 49 vs 21 [46%] of 46, P < .001) and 23% (7 [14%] of 49 vs 17 [37%] of 46, P < .01) for local and distal tumor recurrence, respectively, as reported in Patchell et al's landmark study in 1998 . However, the use of WRBT is limited by an associated increased risk of neurocognitive decline and decreased QOL . As patient survival improves, these long‐term toxicities are becoming less acceptable.…”
Section: The Role Of Adjuvant/neoadjuvant Therapies and Surgerymentioning
confidence: 87%
“…Other studies have reported on the high risk of LMD in patients receiving SRS to the resection cavity, and have cited incidence rates around 12–14% [3234]. Breast cancer metastases have been shown to have a particularly high rate of LMD [3234].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer metastases have been shown to have a particularly high rate of LMD [3234]. Additionally, many studies reported on the adverse side effects of WBRT, including physical symptoms such as alopecia, somnolence, hearing loss, skin changes, and neurocognitive decline, manifested as memory loss and learning impairment [2, 7, 18, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Only previously, several single-institution series have been published with, naturally, not insignificant differences in patients' characteristics as well as dose prescription recommendations [5,[8][9][10][11][12][13][14][15][16][17]. To provide a broader basis and to identify relevant prognostic factors, we pooled the data from two German institutions for Radiation Oncology and present the detailed data on outcome in the present manuscript.…”
Section: Original Researchmentioning
confidence: 99%